Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Harfa, Nuraliyah Azizah; Nurmiati, Nurmiati; Ilham, Ilham (Patria Artha University, 2025)
This research is qualitative research with the aim of finding out: (1) the leadership of school principals at UPT SMP Negeri 6 Lembang; (2) teacher performance at UPT SMP Negeri 6 Lembang; (3) the implementation of the principal's leadership in supporting the performance of teachers in remote areas at UPT SMP Negeri 6 Lembang, Lembang District, Kapubaten Pinrang. The informants consisted of the principal of UPT SMP Negeri 6 Lembang and 10 teachers of UPT SMP Negeri 6 Lembang. Data collection was carried out by observation, interview and documentation techniques. Data analysis is carried out through data reduction, display and data verification. Proving the validity of the data is carried out by extending observations, increasing accuracy in research and triangulation. The results of the research show that: (1) The Principal of UPT SMP Negeri 6 Lembang has carried out his role as an educator, manager, administrator, supervisor, leader, motivator and innovator in the school; (2) the performance of teachers at UPT SMP Negeri 6 Lembang in the process of planning, implementing and evaluating learning in accordance with their duties and responsibilities; (3) The Principal of UPT SMP Negeri 6 Lembang supports the performance of teachers in their role as educators, managers, administrators, supervisors, leaders, motivators and innovators who have been able to support in the process of planning, implementing and evaluating learning in the form of providing information, encouragement in improving the quality of education and monitoring teachers at UPT SMP Negeri 6 Lembang